Biophilia: From A Sociological And Environmental Theory To An Urban And Architectural Approach - Djouad Fatima Zahra; Salah Salah Hana; Bechlem Rayen; Ramdane Meriem (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Bipohilia is a sociological, psychological and environmental theory based on the reality of human beings' close relationship and attachment to nature and natural processes. This behavior is defined through an analytical approach based on the way in which human beings conceive their architectural and urban space, integrating the natural element as a principal element of spatial design. How can the theory of biophilia be introduced as an urban and architectural method and approach? The present work proposes a complex approach to ensure a clear, logical transition that has already been adopted in published scientific articles.